EFFECTS OF SALINITY AND pH ON THE GROWTH OF SEAWATER MICROALGAE IN PHOTOBIOREACTOR (PBR) FOR THE PRODUCTION OF BIODIESEL - MUHAMMAD AFIQ, ZAINAL ABIDIN (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Microalgae is a highly potential feedstock to produce biodiesel that can replace fossil fuels in the future due to its readily availability compared to other feedstock’s such as waste cooking oil, canola and ethanol. Microalgae is highly advantageous because the main sources to cultivate microalgae such as light, water, salinity, pH and carbon dioxide are readily available and abundant in nature. Microalgae is being cultivated through two mechanisms; (i) open raceway pond and (ii) photobioreactor (PBR). This study will focus on the cultivation of microalgae in a small-scale PBR, as it is highly advantageous compared to open raceway pond such as risk of contamination and settling of microalgae. The main objective of this thesis is to study and determine the effects of salinity and pH on the growth of seawater microalgae in PBR for the production of biodiesel. The objective stated will enable a better cultivation culture of microalgae in the PBR to obtain high growth rate of microalgae. Salinity alongside with pH in a PBR is really crucial in the cultivation process of microalgae, as salinity and pH will enhance the growth of microalgae by providing a good environment to enhance its growth. In this study, salinity is varied through 26 to 30 part per thousand (ppt) and the effects of salinity alongside with pH are studied. Nannochloropsis Sp. type of seawater microalgae is taken and cultivated with the aforementioned varied parameters. Nannochloropsis Sp. is cultivated in a small scale (2 Litre) and it is cultivated thorugh its living period of 7 to 10 days. It is shown that, microalgae with a salinity value of 28 ppt shows the highest growth rate in term of its cell density with a pH value ranges between 8.20 and 8.67.